Planning Evacuation Routes as Tsunami Disaster Mitigation in Coastal Makassar City - Singgih, Hanna Mariani; Sufiati Bestari (Journal of Science and Education (JSE), 2024)
The recent series of earthquakes can trigger tsunamis. Coastal areas are highly dynamic and therefore potentially subject to tsunami threats.  Makassar City is a coastal area. Therefore, Makassar City is vulnerable to hit by tsunami, as the increasing stress at the ends of the active plates around Sulawesi Island, which increases the potential for seabed earthquakes, which in turn can cause tsunamis. The absence of a tsunami disaster mitigation concept in the southern coastal area of Makassar city increases the chances of huge losses in the event of a tsunami. The purpose of this research is to map the tsunami disaster mitigation in the southern coastal area of Makassar City. The research method is observational spatial data input and direct observation in the field. All coordinate data and the latest earthquake became the main input in the SiTProS program, while spatial data used ArcGIS Map. The research study area is from The Rinra Hotel (Phinisi Point Mall) to Barombong Stadium. The path along this route will be the location of the proposed Temporary Evacuation Site (TES) route, with the scenario that there are 15 building units that are higher than the maximum wave height at the coastline of 4.29 meters that can be recommended for vertical evacuation. The simulated tsunami propagation time to reach a tsunami detection device (buoy) was 30.586 minutes after a potential tsunami occurred in the Sulawesi Sea at an earthquake of 5.8 SR, and the time to reach the coastline was at 41.44 minutes. The best shortest path for evacuation during a tsunami is away from the Barombong bridge and the Jeneberang River estuary. This study concluded three evacuation routes, namely: (I) the route after Barombong bridge towards the south up to Barombong Stadium; (II) the route after Barombong bridge towards the north up to the bridge after GTC Mall; (III) the route from CPI towards the south up to the bridge before GTC Mall (Danau Tanjung Bunga road). In these evacuation routes, the ones that can be used as alternative routes are route I and route III because they go beyond the coastal boundary. Meanwhile, route II is not recommended as it exceeds the coastal boundary.